CIVIL LIABILITY FOR DAMAGES CAUSED BY ARTIFICIAL INTELLIGENCE: A SYSTEMATIC LITERATURE REVIEW OF THE DOCTRINES OF STRICT LIABILITY, VICARIOUS LIABILITY, AND THE NEED FOR REFORM OF INDONESIAN CIVIL LAW - Gunawan Widjaja (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
The development of artificial intelligence (AI) poses new challenges for Indonesian civil law, particularly regarding the attribution of liability for damages caused by autonomous systems. This systematic literature review analyzes the relevance of the doctrines of strict liability and vicarious liability to AI-related damages, identifies the limitations of the fault-based Articles 1365 and 1367 of the Indonesian Civil Code, and formulates the need for reform of Indonesian civil law. Strict liability is effective for high-risk AI by relieving victims of the burden of proving fault, while vicarious liability is suitable for multi-party ecosystems through the principle of supervision. However, the black-box nature and autonomy of AI demand a risk-based regulatory approach incorporating a presumption of fault, joint liability, and algorithmic transparency obligations. Reform is necessary through an Indonesian AI Liability Directive (lex specialis) amending the Civil Code, strengthening technology-related judicial infrastructure, and ensuring ASEAN harmonization, thereby balancing Industry 5.0 innovation with the protection of human rights.